The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s12560-020-09424-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Hepatitis E Virus Genotype 3 in Wastewater and Urban Surface Waters in Germany

Abstract: In highly populated areas, environmental surveillance of wastewater and surface waters is a key factor to control the circulation of viruses and risks for public health. Hepatitis E virus (HEV) genotype 3 is considered as an emerging pathogen in industrialized countries. Therefore, this study was carried out to determine the prevalence of HEV in environmental waters in urban and suburban regions in Germany. HEV was monitored in water samples using quantitative RT-PCR (RT-qPCR) and nested RT-PCR without or with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 47 publications
3
22
0
4
Order By: Relevance
“…HEV genotype 3 has been detected in wastewater in several studies. 20 All these results show that due to the absence of routine screening of HEV in the health system, HEV infection remains globally unknown in the human population and when this infection becomes symptomatic, the diagnosis is directed toward other diseases as was the case with these patients suspected to having yellow fever virus in 2013. 9 The limit of our study is that the samples used for the amplification had not arrived at the laboratory under the optimal temperature conditions required, which would have influenced the results obtained with a possible degradation of RNA.…”
Section: Discussionmentioning
confidence: 99%
“…HEV genotype 3 has been detected in wastewater in several studies. 20 All these results show that due to the absence of routine screening of HEV in the health system, HEV infection remains globally unknown in the human population and when this infection becomes symptomatic, the diagnosis is directed toward other diseases as was the case with these patients suspected to having yellow fever virus in 2013. 9 The limit of our study is that the samples used for the amplification had not arrived at the laboratory under the optimal temperature conditions required, which would have influenced the results obtained with a possible degradation of RNA.…”
Section: Discussionmentioning
confidence: 99%
“… Ultracentrifugation followed PEG Total of 184 (111 influent and 83 effluent) wastewater samples analysed, 93/111 (84%) influents and 26/83 (31%) effluents. Median 3× 10 3 (influent) and 1× 10 3 (effluent) ( Beyer et al, 2020 ) Mexico Poliovirus Viral nucleic acid obtained from concentrated wastewater samples. Poliovirus serotype detected by qRT-PCR.…”
Section: Virus Detection Methods In Wastewater Systemsmentioning
confidence: 99%
“…HEV presents an incubation period ranging from 2 to 9 weeks and is clinically indistinguishable from hepatitis A. This virus has been detected in wastewater in France ( Miura et al, 2016 , Courault et al, 2017 , Kaas et al, 2019 ), China ( Li et al, 2017 ), Colombia ( Baez et al, 2017 ), Portugal ( Matos et al, 2018 ), Italy ( Di Profio et al, 2019 ), Germany ( Beyer et al, 2020 ), and some other industrialized countries ( Fenaux et al, 2019 ).…”
Section: Viruses: Genomes Classification and Infection Symptomsmentioning
confidence: 99%
“…Similar results were obtained in a Spanish study [ 35 ], which detected HEV genomes only in the influent samples of four WWTPs, with average concentrations of 10 3 genome copies·L −1 . Additionally, a study from de-Beyer et al revealed the presence of the HEV genomes in the effluent samples of several German WWTPs, with an average concentration of 10 3 genome copies·L −1 [ 36 ].…”
Section: Resultsmentioning
confidence: 99%